Chinese culture and relationship marketing in the Chinese construction industry - Yu, Qi Wei. (2008)
A study on the theories of marketing and relationship marketing, the current status of Chinese construction industry, traditional Chinese culture's influence on business culture and relationship marketing in the context of Chinese culture.